THE EFFECT OF SERVICE QUALITY ON BUILDING CUSTOMER SATICFACTION (ALFAMART THERITORIAL OF RETAIL INDUSTRIAL IN BEKASI) - Muhammad Afif Imam Dzaky Saidi; Muratin Muratin; Muhammad Irfan Rahadian Rahadian (ABNUS Publisher, 2022)
The purposes of this study are determine whether service quality is related to customer satisfaction. This type of research is descriptive with a questionnaire as a data source. The population in this study is the number of consumers who buy basic necessities for 3 months totaling 590 people. The sample in this study was 85 respondents, the sampling technique used was accidental sampling, namely the technique of determining the sample based on chance, namely anyone who coincidentally met a researcher who was buying goods which was used as a sample. The analytical tool in this research is simple linear regression. The next stage of the questionnaire data was analyzed by simple linear regression assisted by the SPSS version 17 computer program. The results showed that based on the results of the correlational test the relationship between the service quality variable (X) and customer satisfaction (Y) was 0.244 because the two variables had a significance value greater than 0.05, namely (0.012 > 0.05), then the relationship was stated not linear and it can be concluded that the quality of service (X) with customer satisfaction (Y) there is no linear relationship. Meanwhile, based on the service quality variable test (X), the t-count value is 2293 and the t-table is 0.05 (df=99) with a significance level of 0.024; Thus, t count > t table (2293 > 0.179), but because the significance is greater than 0.05 (0.024 > 0.05), the first hypothesis (H1) is rejected and Ho is accepted, meaning that service quality (X) has positive effect and significant to customer satisfaction (Y).